Analisis Strategi Kreativitas Guru Dalam Pembelajaran Bahasa Arab Di Lembaga Multijenjang Santri Yayasan Baitul Ilmi Pacitan - Dinna Miftah Usilmi; Maulana Purwa Rimba (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
This study examines the creative strategies employed by teachers in Arabic language instruction within the context of a multi-grade classroom at the Baitul Ilmi Foundation in Pacitan as a response to the heterogeneity of students’ abilities. This study employs a descriptive qualitative approach, utilizing data collection techniques such as interviews, observations, and documentation. Data analysis was conducted through data reduction, data presentation, and drawing conclusions to reveal patterns of teaching strategies implemented by teachers. The results of the study indicate that teacher creativity is reflected in four indicators: fluency, flexibility, originality, and elaboration, which support varied and adaptive learning. Learning strategies include systematic planning, the use of communicative and direct methods, the utilization of conventional and digital learning media, differentiation-based classroom management, as well as formative and summative evaluation. The pedagogical approach used is based on constructivism through social interaction, scaffolding, contextualization, and meaningful learning. The context of a multi-level institution indicates heterogeneity in students’ abilities, the integration of formal and pesantren curricula, and the implementation of bi’ah lughawiyah as a language environment. The research results also indicate that teachers’ creativity has a positive impact on improving students’ Arabic language proficiency, learning motivation, and learning independence. Thus, the success of Arabic language learning